Consumo de alcohol y drogas asociado al rendimiento académico en estudiantes de la Carrera de derecho. Universidad Estatal de Bolívar. Período Octubre 2023 – Febrero 2024 - Cuji Pilco, Janeth Marlene (2024)
Globally, there is significant concern about the adverse effects of harmful consumption of alcohol and drugs, especially among young people, in whom an increase in consumption and its impact on academic performance is evident. The objective was to determine the relationship between substance use and academic performance. A quantitative, descriptive, cross-sectional and correlational approach was used with a sample of 248 university students, using specific instruments such as: RAU scale, AUDIT test and CAD-20 questionnaire to measure alcohol and drug use. The results revealed that most of the students are at low risk 63.7%, followed by 25.4% with medium risk, however, there was a group that corresponds to high risk and probable addiction 10.9% of alcohol consumption. While drug use indicated that 29.4% of the students are not at risk, which is positive, followed by 60.1% with a slight risk, 4.0% with moderate risk, 1.6% with substantial risk, and 4.8% with severe but significant risk, which is why it is necessary to carry out interventions to prevent drug use. With respect to academic performance most students show a high level of dedication to study with 73.0%, in academic contributions we have 48.0%, however, a segment of students with difficulties to improve in the organization of didactic resources was identified with 42.7%. These findings underscore the importance of promoting strategies to improve the well-being of university students and prevent the consumption of these substances, thus enhancing academic performance. Globally, there is significant concern about the adverse effects of harmful consumption of alcohol and drugs, especially among young people, in whom an increase in consumption and its impact on academic performance is evident. The objective was to determine the relationship between substance use and academic performance. A quantitative, descriptive, cross-sectional and correlational approach was used with a sample of 248 university students, using specific instruments such as: RAU scale, AUDIT test and CAD-20 questionnaire to measure alcohol and drug use. The results revealed that most of the students are at low risk 63.7%, followed by 25.4% with medium risk, however, there was a group that corresponds to high risk and probable addiction 10.9% of alcohol consumption. While drug use indicated that 29.4% of the students are not at risk, which is positive, followed by 60.1% with a slight risk, 4.0% with moderate risk, 1.6% with substantial risk, and 4.8% with severe but significant risk, which is why it is necessary to carry out interventions to prevent drug use. With respect to academic performance most students show a high level of dedication to study with 73.0%, in academic contributions we have 48.0%, however, a segment of students with difficulties to improve in the organization of didactic resources was identified with 42.7%. These findings underscore the importance of promoting strategies to improve the well-being of university students and prevent the consumption of these substances, thus enhancing academic performance . ALCOHOL, DRUGS, UNIVERSITY STUDENTS, ACADEMIC PERFORMANCE